Study of hydration potential and kinetics of the ferrite phase in iron-rich CAC - Hertel, Tobias; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2016)
With the presence of CA, the hydration kinetics of ferrite phase is influenced and decreased dramatically. Heat flow measurements, QXRD data, and heat flow calculations show concordantly that hydration of ferrite in mix with CA is retarded until the onset of CA hydration and that less ferrite is dissolved. Analysis of the liquid phase of CA paste and CAC-like cement paste displayed significant higher concentrations of Al and Ca compared with pure ferrite paste. Thus, the composition of the liquid phase is set by initial dissolution of CA. We assume that an instant dissolution of the ferrite phase is blocked when solubility equilibrium is dominated by CA. Dissolution of ferrite is only possible after massive precipitation of hydrates and reduction of Ca and Al concentration in the liquid phase.
Keywords: Calcium aluminate cement(D); Calcium aluminoferrite (D); Calorimetry (A); Pore solution (B); X-ray diffraction (B)